The Pharmacological Activity of Jamblang Plant (Syzygium cumini (L) Skeels) Based on Solvent Polarity: A Systematic Literature Review - Laelasari, Tia; Ghofaro Nurul Azzahro; Muhammad Zein Latif; Himyatul Hidayah (HM Publisher, 2023)
In recent years, there has been growing interest in the potential medicinal benefits of Syzygium cumini. This is due in part to the plant's rich content of antioxidants, flavonoids, and other phytochemicals. These compounds have been shown to have a variety of beneficial effects, including antidiabetic, anti-inflammatory, and anti-cancer properties. The solvent plays an important role in the extraction of compounds from Syzygium cumini. This study aimed to conduct a systematic review to explore the potential of jamblang plants (Syzygium cumini) based on solvent polarity. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the potential of jamblang in medicinal uses based on solvent polarity. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. The solvent plays an important role in the extraction of compounds from Syzygium cumini. The solvent must be able to dissolve the target compounds, but it must not also dissolve other compounds that are not desired. The solvent must also be compatible with the plant material and the extraction method. The solvent must be of the same polarity as the target compounds. For example, polar solvents such as water and ethanol are good for extracting polar compounds, such as flavonoids and anthocyanins. Non-polar solvents such as acetone and methanol are good for extracting non-polar compounds, such as terpenes and steroids.